2021
DOI: 10.1177/10778012211014558
|View full text |Cite
|
Sign up to set email alerts
|

Asking the Hard Questions: Psychologists’ Discomfort With Inquiring About Sexual Abuse Histories

Abstract: The literature on sexual abuse indicates low rates of inquiry by mental health professionals. This study explores early career psychologists’ experiences of inquiry into their clients’ sexual abuse histories. Twelve Australian psychologists participated in semi-structured interviews with transcripts analyzed using thematic analysis. The vast majority of participants reported that they did not routinely inquire about sexual abuse with barriers including not knowing what to do, discomfort, stigma, and fear of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that asking these types of questions might cause discomfort for healthcare providers and patients [39]. However, patients with missing data had higher morbidity, frailty, urgency, and mortality (table S2 in the appendix).…”
Section: Original Articlementioning
confidence: 99%
“…Previous studies have suggested that asking these types of questions might cause discomfort for healthcare providers and patients [39]. However, patients with missing data had higher morbidity, frailty, urgency, and mortality (table S2 in the appendix).…”
Section: Original Articlementioning
confidence: 99%
“…Yet, these services' enquiry about sexual violence (historic or current) is often limited (Neill & Read, 2022). Barriers include a belief among healthcare professionals (HCPs) that asking about abuse experiences is not appropriate and not part of their role, fears of re‐traumatising service users, competing workload priorities and feeling under‐skilled to respond to disclosure of sexual violence (Nixon & Quinlan, 2022; O'Dwyer et al., 2019). Inadequate responses to disclosures of sexual violence, including a lack of empathy and insufficient care, have also been identified in statutory services (Bond et al., 2018).…”
Section: Introductionmentioning
confidence: 99%